Development of Bio-Based Materials: Synthesis, Characterization and Applications - Borrero-López, Antonio M.; Valencia-Barragán, Concepción; Cortés Triviño, Esperanza; Tenorio-Alfonso, Adrián; Delgado-Sánchez, Clara (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The need to find suitable biomaterials and procedures from alternative sources able to imitate or even enhance the performance of currently used products has become an important focus of research today due to the depletion of non-renewable resources and the increasing concern related to climate change, sustainability and environmental preservation. Thus, this reprint gathers different original articles and review manuscripts from the Special Issue "Development of Bio-Based Materials: Synthesis, Characterization and Applications". The development of partial or fully bio-based materials has been included, with excellent outcomes in many different applications, as well as alternative procedures that can reduce the carbon footprint or optimize both production and energy consumption.